Change in short distance swimming performance following inspiratory muscle fatigue - Muranaka, M.; Suzuki, Y.; Ando, R.; Sengoku, Y. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Inspiratory muscle fatigue (IMF) may impair performance in a subsequent exercise. A few studies have reported that IMF decreased swimming performance in submaximal intensity or severe intensity domain. However, the impact of IMF on high-intensity short-duration swimming is not clear. The purpose of this study was to clarify the effect of preinduced IMF on extreme intensity domain swimming. METHODS: Seven male competitive swimmers swam two 100-meter all-out front crawl swimming trials with and without preinduced IMF. Maximal inspiratory and expiratory mouth pressure (PImax and PEmax, respectively) was used as indicators of inspiratory and expiratory muscle strength before and after swimming, and stroke parameters during swimming were measured. IMF was achieved by having the subjects breathe against an inspiratory pressure threshold load while generating 40% of their predetermined PImax for 10 minutes. RESULTS: After the induction of IMF, swimming time (55.94±1.15 s) was significantly slower compared with that in control swimming without IMF (54.09±0.91 s) (P<0.05). During swimming followed IMF, a significant decrease in stroke rate and a significant increase in stroke length were observed in the latter half of the 100-meter swimming trial. In addition, the sense of dyspnea was significantly higher in swimming in the IMF condition than in control condition. CONCLUSIONS: IMF prior to swimming negatively affects swimming performance in the extreme intensity domain. It is suggested that due to the dual use of respiration and generate propulsion in accessory respiratory muscles, IMF affected swimmers` ability to maintain swimming velocity.